Leadership and Management Strategies for Creating Agile Universities - Connolly, Thomas, 1957-; Farrier, Stephen, 1951- (Hershey: IGI Global, Information Science Reference, 2022)
"This book critically reflects on the challenges that higher education has faced during the pandemic and how different universities have addressed the challenges and learned from what has worked and not worked offering some suggestions on how the higher education sector might transform itself to ensure it is more capable of dealing with similar challenges in the future"--
Includes bibliographical references and index.
Keywords: Educational change; Educational leadership; Universities and colleges -- Administration -- Planning; Web-based instruction -- Evaluation -- Case studies; COVID-19 Pandemic, 2020- -- Educational aspects